Adapting an Online Transit Journey Planner into a Low-Cost Travel Survey Tool. Issue 1 (January 2014) - Schmitt, Lorelei; Harris, Sally; Currie, Graham
Urban transport authorities worldwide face difficult trade-offs in collecting information on public transit users. The costs of data collection can be high, and the technical challenges in understanding complex travel patterns require substantive survey resources. However, rapid technology advances have yielded improved traveler information tools. The improved tools enable the encoding of complex travel requests in transit journey planners, which are now a common feature of transit passenger information websites (TPIWSs). This paper describes the experience of developing an online survey tool in the journey planner section of a TPIWS as a new mechanism to undertake research in an effective and inexpensive way. The approach integrates information collated from the journey planner outputs and explores passengers' experiences of journeys made on the basis of online surveys. Journey planner outputs were first recorded along with the answers to two simple poll questions. Respondents were then invited to undertake a follow-up survey after they had completed the trips for which they had used the journey planner. A total of 3, 537 polls were submitted, and 658 follow-up surveys were completed. The samples users were in general younger and had characteristics different from those of the general transit market. However, overall the tool proved to be a powerful, easy-to-use, and inexpensive means of collecting information about complex travel behaviors. The lessons learned are described, and approaches are suggested for how on-screen polling could be improved, including computing approaches to manage web pop-up blockers, which are thought to have reduced sample sizes and possibly affected the demographic composition achieved. Implications for industry practice and opportunities for future research in this area are identified.